Lapisan Kedap Buatan untuk Memperkecil Perkolasi Lahan Sawah Tadah Hujan dalam Mendukung Irigasi Hemat Air - Asep Sapei; Muhammad Fauzan (Jurnal Irigasi, 2012)
Irrigation efficiency can be improved at the time of delivery (conveyance), distribution and application. Water losses in the form of evaporation, leakage, seepage, percolation and water waste are reduced to a minimum. The purpose of this study is to examine the role of artificial impervious layer in reducing percolation of paddy field related to water saving irrigation and to improve efficiency. The impervious layer is made by compacting the soil below the plow layer by using soil stamper and baby roller. The impervious layer thickness is obtained about 14 cm and the maximum hardness were 9.41 – 13.28 kg/cm2. The percolation obtained from 7.9 to 21.3 cm/day. Relatively smaller percolation obtained from plot which was compacted by using baby roller. But the obtained percolation is still too big for the paddy field which is only about 4 mm/day. This may be caused by the conditions of the plot that has very high percolation rate (508.8 cm/day).